2018
DOI: 10.1016/j.arth.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

A 2- to 16-Year Clinical Follow-Up of Revision Total Hip Arthroplasty Using a New Acetabular Implant Combined With Impacted Bone Allografts and a Cemented Cup

Abstract: IBG combined with the compressing shell results in excellent results for this challenging condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
0
24
0
2
Order By: Relevance
“…The evidence on which the decision to use a prosthesis to revise a failed PFNA was based was vague and controversial [19]. In addition, the operating specifications for reducing or avoiding mechanical complications were rarely mentioned in the previous literature [7,20].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence on which the decision to use a prosthesis to revise a failed PFNA was based was vague and controversial [19]. In addition, the operating specifications for reducing or avoiding mechanical complications were rarely mentioned in the previous literature [7,20].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted in the orthopedic community that allografts represent a suitable option to address small to large acetabular or femoral bone defects, which represent a common problem in revision procedures (especially revision THA). This notion is primarily based on clinical and radiological evidence with good to excellent outcomes for structural and chip allografts in both the acetabulum 9,19,[30][31][32][33] and the femur 14,19,[34][35][36] . On a histological level, previous studies in the acetabulum were limited to small n-numbers and indicated remained integrity of structural allografts with minimal remodeling 37 .…”
Section: Discussionmentioning
confidence: 99%
“…However, for younger groups, the choice of prosthesis is still controversial [13]. Recent studies [22,19] have shown that CTA devices have noteworthy advantages in terms of functional outcomes and orthopaedic complications for failed PFNAs in young patients compared to UTA devices.…”
Section: Discussionmentioning
confidence: 99%